Explaining the Phenomenon of Therapeutic Deadlock in Infertile Women: A Qualitative Phenomenological Study - Somayeh Souri; Behzad Imani; Maryam Maddineshat (Obstetrics and Gynecology International)
Conclusion: This study examines the phenomenon of therapeutic deadlock among infertile women, highlighting how their cultural and social contexts shape their treatment choices. Despite facing hesitations and potential risks, these women seek treatment in various ways. When confronted with a deadlock in their journey, they often experience negative thoughts and employ different coping strategies, which range from resistance to faith in a higher power and sometimes surrendering to fate.